Analysis of Health Service Quality and Patient Satisfaction Among Hypertension Patients in Samarinda - Sayyid Muhammad Taqie; Ratno Adrianto (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Hypertension is one of the most common non-communicable diseases in Indonesia and requires long-term, continuous care. The Sungai Siring Community Health Center in North Samarinda records a high number of hypertensive patient visits every month. However, preliminary findings revealed several service issues, such as long waiting times, limited communication between patients and health workers, and lack of coordination among service units. These problems indicate a gap between patients’ expectations and the actual quality of services. Improving service quality is essential because it directly affects patient satisfaction, adherence to treatment, and continuity of care Objective : To analyze the relationship between the seven WHO dimensions of healthcare service quality—safety, effectiveness, timeliness, patient-centeredness, efficiency, equity, and integration— and patient satisfaction among hypertensive patients at the Sungai Siring Community Health Center, Samarinda. This study used an analytical observational design with a cross-sectional approach. A total of 139 hypertensive patients were selected through accidental sampling. Data were collected using a structured questionnaire covering respondent characteristics, assessments of the seven service quality dimensions, and patient satisfaction levels. The data were analyzed using the Chi-Square test with a significance level of 0.05 Results : All seven dimensions of service quality showed a significant relationship with patient satisfaction (p = 0.001) Conclusion/Lesson Learned : Effectiveness and timeliness were the most influential dimensions. Providing effective, timeliness, efficient, and patient-centered care and integration can increase patient trust, loyalty, and adherence to hypertension treatment at the community health center.